2008
DOI: 10.1016/j.virusres.2007.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Human immunopathogenesis of severe acute respiratory syndrome (SARS)

Abstract: Progressive immune-associated injury is a hallmark of severe acute respiratory syndrome (SARS). Viral evasion of innate immunity, hypercytokinemia and systemic immunopathology in the SARS coronavirus (SARS CoV) infected host have been suggested as possible mechanisms for the cause of severe pathology and morbidity in SARS patients. The molecular and cellular basis for how SARS CoV impacts the host immune system resulting in severe SARS, however, has not been elucidated. The variable clinical course of SARS may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
335
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(355 citation statements)
references
References 39 publications
10
335
0
10
Order By: Relevance
“…Since MA15-infected mice had lower mortality than v2163-infected mice, MIP-1α and RANTES may not be good indicators of disease outcome. When comparing the mouse cytokine profile to that detected in human SARS patients, the majority of human studies showed the same profile as seen in mice for IL-2, IL-4, IL-6, IL-10, IFN-γ, TNF-α, IP-10 and MCP-1 (Cameron et al, 2008; Chen and Subbarao, 2007; Hsueh et al, 2004; Zhu, 2004)(Table 6). In contrast, IL-1β was not elevated in mouse lungs or in human lungs, but 3 of 5 serum studies reviewed showed elevated IL-1β in human patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Since MA15-infected mice had lower mortality than v2163-infected mice, MIP-1α and RANTES may not be good indicators of disease outcome. When comparing the mouse cytokine profile to that detected in human SARS patients, the majority of human studies showed the same profile as seen in mice for IL-2, IL-4, IL-6, IL-10, IFN-γ, TNF-α, IP-10 and MCP-1 (Cameron et al, 2008; Chen and Subbarao, 2007; Hsueh et al, 2004; Zhu, 2004)(Table 6). In contrast, IL-1β was not elevated in mouse lungs or in human lungs, but 3 of 5 serum studies reviewed showed elevated IL-1β in human patients.…”
Section: Discussionmentioning
confidence: 69%
“… + = cytokine elevated 0 = cytokine not elevated ND = not determined a Source: Chen and Subbarao, 2007 b Sources: Hsueh et al, 2004; Cameron et al, 2008, Review of Chen and Subbarao, 2007, review of Zhu, 2004. c Separate study currently in press. …”
Section: Figures and Tablesmentioning
confidence: 99%
“…The increased concentration of proinflammatory cy-272 tokines (eg, TNF-α, IL-1β and IL-6) in BALF has been noted to be in 273 accordance with the severity of ALI [13,14]. Continuous elevation of 274 the cytokines mentioned above in patients suffering from ALI indicated 275 a poor outcome[32]. These proinflammatory cytokines magnify the…”
mentioning
confidence: 99%
“…Viruses may differ substantially in the amount of host cell damage they cause during their replication (7,17,57,62,67). The immune response presents a powerful barrier against viruses and can target both cell-free viruses and virus-infected cells.…”
mentioning
confidence: 99%